Successful Spatial Development Requires Comprehensive Mobility, Represented on an Example of a Middle Centre in China - Martin, Ullrich (Promet - Traffic&Transportation, 2003)
Increasing demand of traffic is in strong interaction withspatial as well as economic development. The resulting problemsparticularly appear in countries with high population densityand high development potential. New solutions are necessaryto ensure long-term successful development, which arealso of great interest for developed industrialised countries tomanage traffic problems.